Edwardsiella ictaluri evpP is required for colonisation of channel catfish ovary cells and necrosis in anterior kidney macrophages. (20th December 2019) - Kalindamar, Safak; Kordon, Adef O.; Abdelhamed, Hossam; Tan, Wei; Pinchuk, Lesya M.; Karsi, Attila
Abstract: Edwardsiella ictaluri is a Gram‐negative facultative anaerobe that can survive inside channel catfish phagocytes. E. ictaluri can orchestrate Type VI Secretion System (T6SS) for survival in catfish macrophages. evpP encodes one of the T6SS translocated effector proteins. However, the role of evpP in E. ictaluri is still unexplored. In this work, we constructed an E. ictaluri evpP mutant ( Ei Δ evpP ) and assessed its survival under complement and oxidative stress. Persistence of Ei Δ evpP in catfish as well as attachment and invasion in catfish macrophage and ovary cells were determined. Further, virulence of Ei Δ evpP in catfish and apoptosis it caused in macrophages were explored. Ei Δ evpP behaved same as wild type ( Ei WT) under complement and oxidative stress in complex media, whereas oxidative stress affected mutant's survival significantly in minimal media ( p < .05). Persistence of Ei Δ evpP in live catfish and uptake and survival inside peritoneal macrophages were similar. The attachment and invasion capabilities of Ei Δ evpP in catfish ovary cells were significantly less than that of Ei WT ( p < .05). Although Ei Δ evpP showed reduced attenuation in catfish, causing decreased catfish mortality compared with Ei WT (44.73% vs. 67.53%), this difference was not significant. The apoptosis assay using anterior kidney macrophages indicated that the number of live macrophages exposed to Ei Δ evpP was significantly higher compared with Ei WT exposed macrophages at 24‐hr post‐treatment ( p < .05). However, there were no significant differences in the early and late apoptosis. Remarkably, necrosis in Ei Δ evpP exposed macrophages was significantly less than that of Ei WT exposed macrophages at 24 hr ( p < .05). Our results demonstrated that evpP is required for colonisation of catfish ovary cells and increased apoptosis and necrosis in anterior kidney macrophages.